A case report on facial subcutaneous dirofilariasis with intraoral extension - Malviya, Vikas; Goyal, Sakshi (International Surgery Journal, 2020)
Dirofilarial is parasitic nematodes of domestic and wild animals that can infect humans accidently via vectors. This disease is endemic in South Eastern United States, Australia, Europe and Central and Southern Asia. Dirofilaria immitis and Drepens are the common mosquito borne filarial nematodes that cause infection. The most frequent presentation of human dirofilariasis is a single submucosal nodule without signs of inflammation. Oral dirofilariasis is extremely rare and only a few cases have been documented. We report an interesting case of subcutaneous dirofilariasis in a patient who presented with a facial swelling. Laboratory investigations and radiographs were non-contributory to diagnosis. This paper stresses the importance of considering dirofilariasis as differential diagnosis for subcutaneous swelling of the face with intraoral extension, especially in areas where it is endemic.